The suppression of the Congo rebellions and the rise of Mobutu, 1963–5. Issue 1 (1st January 2017) - De Witte, Ludo
ABSTRACT: The first years of the Congo as an independent state were marked by instability and rebellion as local nationalist struggles became embroiled in what NATO powers feared could lead to the loss of hegemony over the country and its vast mineral wealth, if not into a theatre of Cold War politics. This article focuses on the series of rebellions, including the Mulelist revolt and the Simba uprising, that took place in the Congo from late 1963 into 1965. Belgian, British, and US diplomatic and Congolese military sources are used to analyse the intervention of the West against the Congolese rebels, in support of the Congo government in Léopoldville headed by Prime Minister Tshombe and President Kasa Vubu. Belgian, US, and Congolese sources on this military campaign led by Belgian officers, known as 'the Ommegang', allow a detailed analysis of the planning and execution of the assault on the rebel stronghold Stanleyville by Belgian officers, white mercenaries and the forces of the Congo Army, including the decision to deploy Belgian parachutists, dropped by US aircraft. These events culminated in the coup that brought Mobutu to political power in Congo in November 1965, marking out the trajectory of the county's history for the next three decades.